GABA Neuronal Deletion of Shank3 Exons 14–16 in Mice Suppresses Striatal Excitatory Synaptic Input and Induces Social and Locomotor Abnormalities - Yoo, Taesun; Cho, Heejin; Lee, Jiseok; Park, Haram; Yoo, Ye-Eun; Yang, Esther; Kim, Jin Yong; Kim, Hyun; Kim, Eunjoon (Frontiers in Cellular Neuroscience, 2018)
Shank3 is an excitatory postsynaptic scaffolding protein implicated in multiple brain disorders, including autism spectrum disorders and Phelan-McDermid syndrome. Although previous neurobiological studies on Shank3 and Shank3-mutant mice have revealed diverse roles of Shank3 in the regulation of synaptic, neuronal, and brain functions, whether Shank3 expression in specific cell types distinctly contributes to mouse phenotypes remains largely unclear. In the present study, we generated two Shank3-mutant mouse lines (exons 14–16) carrying global and GABA neuron-specific deletions and characterized their electrophysiological and behavioral phenotypes. These mouse lines show similar decreases in excitatory synaptic input onto dorsolateral striatal neurons. In addition, the abnormal social and locomotor behaviors observed in global Shank3-mutant mice are strongly mimicked by GABA neuron-specific Shank3-mutant mice, whereas the repetitive and anxiety-like behaviors are only partially mimicked. These results suggest that GABAergic Shank3 (exons 14–16) deletion has strong influences on striatal excitatory synaptic transmission and social and locomotor behaviors in mice.